Synthesis of (-)-(Z)-deoxypukalide. - Donohoe, T; Ironmonger, A; Kershaw, N (2008)
(Chemical Equation Presented) Closing the deal: A ring-closing metathesis (RCM)/aromatization protocol, followed by a regioselective Negishi cross-coupling reaction and macrolactonization, with subsequent RCM mediate the synthesis of (-)-(Z)-deoxypukalide in 12 linear steps and 15% overall yield (see retrosynthesis; TBS=tert-butyldimethylsilyl, TIPS=triisopropylsilyl). © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.